WARIA DAN RESILIENSI TERHADAP PENOLAKAN MASYARAKAT - Baihaqi; Mutia Tisa (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This article discusses the resilience of transsexuals to community rejection. Transexuality is a social phenomenon in society. Not only because of gender, it also a matter of their attitudes and behavior that incline towards feminism. Therefore, most people in society do not accept the presence of those transsexuals. Even among their own families their change of identity is not acceptable. The writer uses descriptive qualitative research to explain the obtained phenomenon about the resilience of the transsexuals. The data are obtained based on interviews, documentation and literature. It is explained that basically there are some people who accept and reject the presence of transsexuals, but bullying, discrimination, family rejection and others contribute to the process of these transsexualse resilience. It might occur because some people consider identity change of the transsexuals is unnatural, although basically many factors may cause a person to change their identity into a transsexual, including the environment, family and social life. Hence, it is undeniable that there needs to be some solutions to those problems. in order to create a life without discrimination for the transsexuals